Individual-based modeling of potential poliovirus transmission in connected religious communities in North America with low uptake of vaccination - Kisjes, Kasper H. (J Infect Dis, 2014)
BACKGROUND: Pockets of undervaccinated individuals continue to raise concerns about their potential to sustain epidemic transmission of vaccine preventable diseases. Prior importations of live polioviruses (LPVs) into Amish communities in North America led to their recognition as a potential and identifiable linked network of undervaccinated individuals. METHODS: We developed an individual-based model to explore the potential transmission of a LPV throughout the North American Amish population. RESULTS: Our model demonstrates the expected limited impact associated with the historical importations, which occurred in the context of a high level of population immunity attributable to historical exposure to LPVs (wild and vaccine). We show that some conditions could potentially lead to wider circulation and paralytic cases in Amish communities if an importation occurred in or after 2013. The impact will depend on the uncertain historical immunity of members of the community to polioviruses. CONCLUSIONS: Heterogeneity in immunization coverage represents a risk factor for potential outbreaks of polio if a live virus introduction occurs, although overall high population immunity suggests that transmission would remain relatively limited. Efforts to prevent spread between Amish church districts with any feasible measures may offer the best opportunity to contain an outbreak and limit its size.